THE MUMMY in context - Richard Freeman (European Journal of American Studies)
This article examines the literary and cinematic antecedents of a cinema icon, The Mummy, produced by Universal Pictures in 1932.  It looks at the sources in Victorian and Edwardian literature to see if any of the ideas found their way into the film.  Similarly, the silent cinema is surveyed to see if the 1932 film was a collection of previously filmed stories remoulded.  The context of the Great Depression and its effects on Universal Studios will be shown to have a significant influence on the decision to make the film.  The film itself and its publicity is discussed, followed by its reception at the time, and its significance to writers since.